PENERAPAN MEDIA PEMBELAJARAN POP-UP BOOK ANIMATION UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPAS MATERI SISTEM PERNAPASAN KELAS V UPT SDN 5 TAROWANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is whether the application of pop-up book animation learning media can improve learning outcomes in the science subject of fifth-grade students at UPT SDN 5 Tarowang. This study aims to apply pop-up book animation learning media to improve learning outcomes in the science subject of fifth-grade students at UPT SDN 5 Tarowang. This type of research is classroom action research consisting of two cycles, each cycle conducted four meetings. The research procedure includes planning, action implementation, observation, and reflection. The subjects in this study were 15 fifth-grade students at UPT SDN 5 Tarowang. The results showed that the application of Pop-Up Book Animation learning media can improve student learning outcomes. In Cycle I, 7 students (47%) achieved learning mastery, while 8 students (53%) did not achieve mastery. These results indicate that classical learning mastery has not been achieved. After improvements were made in Cycle II, student learning outcomes improved, with 12 students achieving learning completion (80%) and 3 students achieving completion (20%). Therefore, classical learning completion has been achieved. Based on these research results, it can be concluded that the application of Pop-Up Book Animation learning media can improve student learning outcomes in the subject of Natural Sciences (IPAS) on the respiratory system for fifth-grade students of UPT SDN 5 Tarowang.